GE_GERICHTE P/26385/2017 vom 14. Dezember 2018 - GE Cour de justice (2018)
DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL); FIXATION DE LA PEINE ; FRAIS JUDICIAIRES | CP.144.al1; CP.139.ch1; CP.286.al1; CP.46.al1; CPP.428.al3; CPP.426